Double Barreled Wet Colostomy: Initial Experience and Literature Review. (2nd December 2014) - Salgado-Cruz, Luis; Espin-Basany, Eloy; Vallribera-Valls, Francesc; Sanchez-Garcia, Jose; Jimenez-Gomez, Luis Miguel; Marti-Gallostra, Marc; Garza-Maldonado, Ana
Abstract : Background . Pelvic exenteration and multivisceral resection in colorectal have been described as a curative and palliative intervention. Urinary tract reconstruction in a pelvic exenteration is achieved in most cases with an ileal conduit of Bricker, although different urinary reservoirs have been described. Methods . A retrospective and observational study of six patients who underwent a pelvic exenteration and urinary tract reconstruction with a double barreled wet colostomy (DBWC) was done, describing the preoperative diagnosis, the indication for the pelvic exenteration, the complications associated with the procedure, and the followup in a period of 5 years. A literature review of the case series reported of the technique was performed. Results . Six patients had a urinary tract reconstruction with the DBWC technique, 5 male patients and one female patient. Age range was from 20 to 77 years, with a medium age 53.6 years. The most frequent complication presented was a pelvic abscess in 3 patients (42.85%); all complications could be resolved with a conservative treatment. Conclusion . In the group of our patients with pelvic exenteration and urinary tract reconstruction with a DBWC, it is a safe procedure and well tolerated by the patients, and most of the complications can be resolved with conservative treatment.